Quantized space-time and its influence on two physical problems - 马孟森 赵惠华 (Chinese physics C, 2014)
Based on Snyder＇s idea of quantized space-time, we derive a new generalized uncertainty principle and new modified density of states. Accordingly, we discuss the influence of the modified generalized uncertainty principle on the black hole entropy and the influence of the modified density of states on the Stefan-Boltzman law.